2020
DOI: 10.1002/lary.29098
|View full text |Cite
|
Sign up to set email alerts
|

Using Augmented Reality to Reduce Fear and Promote Cooperation During Pediatric Otolaryngologic Procedures

Abstract: This case series examines interactive AR during minor otolaryngologic procedures. Although VR has been successfully used for pediatric vascular access, removing children from comforting people in the real world has resulted in patient anxiety. AR offers a potential advantage, utilizing distracting holographic images when patients maintain eye contact with parents. The primary objective was to determine the effect of AR on fear during pediatric otolaryngologic procedures. Secondary objectives included evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The earliest procedures that relied on virtual reality involved wound and burn care with patients immersed in a virtual reality application called SnowWorld [44]. Since then, pediatric patients have successfully undergone numerous procedures using virtual reality with little-to-no sedation including mediastinal mass biopsies, hormone suppository implantations, abscess drainages, nasal endoscopies, laceration repairs, lumbar punctures, and central line placements [24,45 ▪ ,46 ▪▪ ,47 ▪ ,48 ▪▪ ].…”
Section: Periprocedural Care With Virtual Realitymentioning
confidence: 99%
“…The earliest procedures that relied on virtual reality involved wound and burn care with patients immersed in a virtual reality application called SnowWorld [44]. Since then, pediatric patients have successfully undergone numerous procedures using virtual reality with little-to-no sedation including mediastinal mass biopsies, hormone suppository implantations, abscess drainages, nasal endoscopies, laceration repairs, lumbar punctures, and central line placements [24,45 ▪ ,46 ▪▪ ,47 ▪ ,48 ▪▪ ].…”
Section: Periprocedural Care With Virtual Realitymentioning
confidence: 99%
“…In most previous studies on VR, patients are asked to use VR just before the surgery 24 and, when reported, the time during which children keep their VR headset on is about 5 min. Perhaps due to the AR glasses being less bothersome (and less heavy), patients in our study wore their AR glasses for 51 min on average 16,17 . That patients willingly use AR for a longer period allows developers to include educational content and more interactive virtual objects.…”
Section: Discussionmentioning
confidence: 86%
“…Perhaps due to the AR glasses being less bothersome (and less heavy), patients in our study wore their AR glasses for 51 min on average. 16,17 That patients willingly use AR for a longer period allows developers to include educational content and more interactive virtual objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,38 There have been studies demonstrating benefit of VR as distraction analgesia or anxiolysis in other otolaryngology procedures as well, including laryngotracheal interventions, 79 endoscopic nasal debridement, 80 and pediatric nasal endoscopy. 81,82 Functional magnetic resonance imaging studies have shown that VR immersion decreases brain activity in regions associated with pain perception, underscoring the basis of VR distraction analgesia. 83,84 For FPRS procedures, a major limitation of using VR for analgesia is that HMDs may obstruct access to much of the upper and midface.…”
Section: Distraction Analgesiamentioning
confidence: 99%